ANALISIS PERKEMBANGAN MORAL PESERTA DIDIK KELAS X SMA NEGERI 9 PONTIANAK - Putri Hartati; Purwanti Purwanti; Ana Fergina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to analyze the moral development of class X SMA Negeri 9 Pontianak. The method used is descriptive method with survey. The population study was 183 people with a sample of 35 students of class X SMA Negeri 9 Pontianak. The data technique use direct communication and indirect. Data aids using questionnaires and interviews. The results are in the moral development of class X students of SMA Negeri 9 Pontianak showing a fairly high category, namely the proportion of 72.46% according to the three existing aspects. The level of pre-conventional moral development in the category of "Low", the proportion of 58.57% with the orientation of the orientation and relative instruments, the conventional category of the "High enough" proportion of 71.70% with the orientation of agreement between personal and law and order orientation, Postconventional category of the proportion of "Very High" 91 , 08% with a legality contact orientation and a universal ethical principle orientation.Keywords: Perkembangan Moral